Pengaruh Kemampuan Komunikasi dan Kecerdasan Emosional Terhadap Kinerja Karyawan dimediasi Disiplin Kerja pada PT. Gasina Makassar - Rahmat Hidayat; Mappamiring; Yana Fajriah (Movere Journal, 2026)
This research is motivated by the important role of human resources in achieving organizational goals, particularly how communication skills, emotional intelligence, and work discipline can affect employee performance. The purpose of this research is to analyze the influence of communication skills, emotional intelligence, and work discipline on employee performance, the influence of communication skills and emotional intelligence on work discipline, and the influence of communication skills and emotional intelligence on employee performance through work discipline. This type of research uses a quantitative approach with a survey method. Data was collected through a questionnaire distributed to 86 employees of PT Gasina Makassar, and then analyzed using path analysis techniques with the help of Smart-PLS 4.0 statistical software. The conclusion of this study is that emotional intelligence and work discipline are the dominant factors influencing employee performance, while communication skills only have a significant impact on performance when mediated by work discipline. These findings imply that the company needs to enhance emotional intelligence, strengthen discipline, and build effective communication to improve employee performance.